2020
DOI: 10.12688/wellcomeopenres.15524.2
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of language laterality assessed by functional transcranial Doppler ultrasound: a twin study

Abstract: Prior studies have estimated heritability of around 0.25 for Background: the trait of handedness, with studies of structural brain asymmetry giving estimates in a similar or lower range. Little is known about heritability of functional language lateralization. This report describes heritability estimates using functional language laterality and handedness phenotypes in a twin sample previously reported by Wilson and Bishop (2018).The total sample consisted of 194 twin pairs (49% monozygotic) Methods: aged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In one study using whole hemispheres, the majority of participants showed left-hemisphere dominance (67/82; 81.7%), with a higher rate of left-hemisphere dominance amongst right-handers than lefthanders [210]. fTCD methods have mostly used the approach of Deppe and colleagues [211], but recent work has raised the question of whether searching for the peak blood flow difference artificially creates distributions that are more bimodal, resulting in a 'notch' at zero, so that it is better to use mean blood flow difference [212] (see https://osf.io/tfyk3/ accessed on 3 November 2021). Wada results have been interpreted in terms of the WLI, Wada Laterality Index, although there are several versions of the index [213].…”
Section: Laterality Coefficients For Assessment Of Language Lateralis...mentioning
confidence: 99%
See 1 more Smart Citation
“…In one study using whole hemispheres, the majority of participants showed left-hemisphere dominance (67/82; 81.7%), with a higher rate of left-hemisphere dominance amongst right-handers than lefthanders [210]. fTCD methods have mostly used the approach of Deppe and colleagues [211], but recent work has raised the question of whether searching for the peak blood flow difference artificially creates distributions that are more bimodal, resulting in a 'notch' at zero, so that it is better to use mean blood flow difference [212] (see https://osf.io/tfyk3/ accessed on 3 November 2021). Wada results have been interpreted in terms of the WLI, Wada Laterality Index, although there are several versions of the index [213].…”
Section: Laterality Coefficients For Assessment Of Language Lateralis...mentioning
confidence: 99%
“…However, as Ooki says in a review, "sample sizes are still not very large and hence the statistical power is insufficient" [310] (p. 4). The heritability of language dominance in twins has been assessed using fTCD, but the confidence interval is very wide, and is compatible with that of handedness in general, but the authors also emphasise its relatively low effect size with a confidence interval ranging upwards from zero [212].…”
Section: Twin and Family Twin Datamentioning
confidence: 99%
“…While many brain asymmetries were strong and directional at the population level, their heritabilities were low. This suggests that genetic-developmental mechanisms for brain asymmetry are tightly constrained and largely genetically invariant in the population, and that environmental factors and/or developmental randomness are responsible for most variability 22,[82][83][84] . A cytoskeleton-based origin of brain asymmetry would fit this scenario, as the cytoskeleton is essential for fundamental functions in cellular biology, beyond axis formation 85,86 .…”
mentioning
confidence: 99%
“…In the case of handedness, developmental noise and randomness are suggested to play a major role in its ontogenesis, are supposed to be under the control of the C allele in the DC model . Stochastic variations are also discussed in Bishop and Bates (2020) regarding language lateralization. Mitchell (2018) provides an overview of the influence of randomness on handedness, but also on other phenotypes like intelligence, personality, and neurodevelopmental disorders.…”
Section: Thesis Conclusionmentioning
confidence: 99%